Respostas
respondido por:
1
(x² - 5x + 3)/3 = (2x + 11)/3
Multiplica por 3 de ambos os lados, teremos:
x² - 5x + 3 = 2x + 11
Rearruma os termos e aplica a fórmula de Báskhara:
x² - 5x - 2x + 3 - 11 = 0 =>
x² - 7x - 8 = 0 =>
a=1 b=-7 c=-8
DELTA = b² - 4*a*c =>
DELTA = (-7)² - 4*1*(-8) =>
DELTA = 49 - (-32) =>
DELTA = 49 + 32 =>
DELTA = 81
x = [-b +- raiz(DELTA)]/2*a =>
x= [7+-raiz(81)]/2*1
Xi= (7+9)/2 = 16/2 = 8 Xii= (7-9)/2 = -2/2 = -1
Multiplica por 3 de ambos os lados, teremos:
x² - 5x + 3 = 2x + 11
Rearruma os termos e aplica a fórmula de Báskhara:
x² - 5x - 2x + 3 - 11 = 0 =>
x² - 7x - 8 = 0 =>
a=1 b=-7 c=-8
DELTA = b² - 4*a*c =>
DELTA = (-7)² - 4*1*(-8) =>
DELTA = 49 - (-32) =>
DELTA = 49 + 32 =>
DELTA = 81
x = [-b +- raiz(DELTA)]/2*a =>
x= [7+-raiz(81)]/2*1
Xi= (7+9)/2 = 16/2 = 8 Xii= (7-9)/2 = -2/2 = -1
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás